“NASH-Worldwide the Commonest Aetiology of Liver Cirrhosis”- a Review Article (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
NAFLD is defined by the presence of fat in the liver (>5% hepatocytes show macrovesicular steatosis) without evidence of other causes of fat accumulation in the liver such as alcohol use (< 20 g/d for women and